2012
DOI: 10.12693/aphyspola.121.a-61
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Infrasound on the Alpha Rhythm of EEG Signal

Abstract: The alpha waves were rst registered and named by Berger in 1929. They are oscillations in the frequency range 812 Hz, originating from the occipital lobe during wakeful relaxation with closed eyes. The alpha blockage is the result of desynchronisation of the bioelectric activity of the brain induced by sensory stimulation. When the subject's eyes are closed, the alpha rhythm is generated. As soon as the eyes are open, alpha disappears. This is called alpha block and may be elicited also by any form of sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…We expected that studying a relationship between the perception of and the brain's response to IS and LF sounds might allow in the future a better understanding of individual complaint cases attributed to these sounds. Kasprzak (2012) examined the effect of airborne IS stimulation (7 Hz at 120 dB SPL; well above threshold according to (Møller, Pedersen, 2004)) on electroencephalography (EEG) patterns and found a significant reduction in the alpha (8-12 Hz) rhythm power when subjects were stimulated by IS. A similar result was found by Kasprzak (2013) using very narrowband (4-8 Hz) IS noise.…”
Section: Introductionmentioning
confidence: 99%
“…We expected that studying a relationship between the perception of and the brain's response to IS and LF sounds might allow in the future a better understanding of individual complaint cases attributed to these sounds. Kasprzak (2012) examined the effect of airborne IS stimulation (7 Hz at 120 dB SPL; well above threshold according to (Møller, Pedersen, 2004)) on electroencephalography (EEG) patterns and found a significant reduction in the alpha (8-12 Hz) rhythm power when subjects were stimulated by IS. A similar result was found by Kasprzak (2013) using very narrowband (4-8 Hz) IS noise.…”
Section: Introductionmentioning
confidence: 99%
“…Tests were carried out on a group of 32 participants. The experiment showed that infrasounds of frequency f = 7 Hz and acoustic pressure level = 120 dB (HP) cause a statistically signicant reduction of the alpha rhythm power [7].…”
Section: Introductionmentioning
confidence: 99%
“…That is undesirable and should be estimated. The authors undertook the research to diagnose the plausible side effect of structure-born noise of such barriers because it may influence human body (Kasprzak, 2014). As a mechanical structure, the acoustic barrier is characterized by mechanical parameters which, in the field of modal analysis, are made up of natural frequencies, damping factors and mode shapes.…”
mentioning
confidence: 99%